Mild evaporative cooling applied to the torso provides thermoregulatory benefits during running in the heat. (June 2015) - Filingeri, D.; Fournet, D.; Hodder, S.; Havenith, G.
Abstract : We investigated the effects of mild evaporative cooling applied to the torso, before or during running in the heat. Nine male participants performed three trials: control‐no cooling (CTR), pre‐exercise cooling (PRE‐COOL), and during‐exercise cooling (COOL). Trials consisted of 10‐min neutral exposure and 50‐min heat exposure (30 °C; 44% humidity), during which a 30‐min running protocol (70% VO2max ) was performed. An evaporative cooling t‐shirt was worn before the heat exposure (PRE‐COOL) or 15 min after the exercise was started (COOL). PRE‐COOL significantly lowered local skin temperature ( T sk ) (up to −5.3 ± 0.3 °C) ( P  < 0.001), mean T sk (up to −2 ± 0.1 °C) ( P  < 0.001), sweat losses (−143 ± 40 g) ( P  = 0.002), and improved thermal comfort ( P  = 0.001). COOL suddenly lowered local T sk (up to −3.8 ± 0.2 °C) ( P  < 0.001), mean T sk (up to −1 ± 0.1 °C) ( P  < 0.001), heart rate (up to −11 ± 2 bpm) ( P  = 0.03), perceived exertion ( P  = 0.001), and improved thermal comfort ( P  = 0.001). We conclude that the mild evaporative cooling provided significant thermoregulatory benefits during exercise in the heat. However, the timing of application was critical in inducing different thermoregulatory responses. These findings provide novel insights on the thermoregulatory role of T sk during exercise in the heat.